A STEP TOWARDS INNOVATION - Kuchkarova, Gavkhar (University Research Base, 2024)
This article explores the potential of a new approach to education to foster innovation and prepare students for the 21st century. It discusses the importance of personalized learning, critical thinking, problem-solving, creativity, and social and emotional learning. The article also presents case studies of innovative educational approaches from around the world, including Finland, the United States, India, Singapore, and Australia.